Exploration of Plastic Degrading Bacteria in the Musi River, PalembangCity - Widjajanti, Hary; Annisa Kemala Tasya; Laila Hanum (Faculty of Science and Technology Universitas Islam Negeri Raden Fatah Palembang, 2025)
Musi River is a waterway in South Sumatra that faces increasing plastic pollution, threatening aquatic ecosystems and human life. This study aims to identify and evaluate plastic-degrading bacteria from Musi River using phenotypic and molecular approaches. The methods of this study include bacterial isolation, plastic degradation test, and Scanning Electron Microscopy (SEM) analysis were carried out to assess degradation efficiency and changes in surface morphology, phenotypic and molecular identification. The results showed that isolates S1I3, S1I5, and S2I1 had high plastic degradation potential, with levels of 38.03%, 34.73%, and 30.46%, respectively. SEM observations showed changes in surface morphology, including pores and cracks. Molecular identification confirmed that S1I3 was Bacillus proteolyticus (99.87%), while S1I5 and S2I1 matched Bacillus cereus (100%).